Continuous education as the basis of sociocultural adaptation - Borinshteyn, Evgenij; Orlenko, Irina (ScienceRise: Pedagogical Education, 2020)
The relevance of the study is due to the demand for universal, heuristic over-professional skills that allow a person to be successful and competitive in today's labor market. Today, an important factor in the success of transformations is the ability to constantly adapt, which may be possible if the quality of the continuing education system is maintained. Therefore, we consider the content of education, bearing in mind a set of specially selected, socially significant and necessary knowledge, abilities and skills, the acquisition of which is necessary for the formation of an individual and the active inclusion of it in society. The purpose of our study is to determine the role of sociocultural adaptation in the continuing education of a person with the high competitive ability in today's society. It is in this, first of all, the value of a professional mobile person. The study outlines the main functions of continuing education and highlights the three main super-professional skills that enable one to be successful and competitive in today's job market. The authors describe the experience of effective cooperation with representatives of various socio-economic professions, potential employers, specialists, parents, students, which allows not only practical skills in the chosen profession to students, but also to learn new technologies, knowledge of professional tools and methods, necessary for innovative activity of specialists. The result of the successful interconnection of sociocultural adaptation and socialization of the modern person is the willingness to constantly raise the educational level, the need to realize their personal potential, the ability to independently acquire new knowledge and skills. The most important task of continuous education is to create the conditions for personal and professional growth of a person, the development of his/her creative, creative abilities, professional competence in the conditions of modern society. The proposed research contributes to the formation of a system of continuous education, which focuses on the continuous restoration and preservation of existing labor resources through the creation of a system of social elevators, the creation of a system of quality continuing education, which corresponds to the competencies of the modern advanced society, the expansion of a system of free continuous education with mandatory 100% internet access to Ukraine at 4G and above, enhancing the prestige of higher education and creating a much larger number of free places in SVR in each region of Ukraine